Aproximación epigenética al efecto de la estimulación auditiva sobre el BDNF en el hipocampo de ratas wistar (2016)
"The aim of this work was to evaluate whether the high frequency musical stimulation could induce the same anxiolytic effect in rats and if such effect, if any, would be related to epigenetic changes in BDNF, specifically in the exon IV methylation. Male Wistar rats were assigned to one of four conditions: control, high frequency music (Mozart K.448), non-transposed frequency music (Mozart K.448) or white noise. Animals were exposed to thelr respective stimuli for 21 consecutive days and the anxiety levels were tested with the elevated plus-maze". -- Tomado del resumen.